PENERAPAN SISTEM AKUNTANSI DALAM PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN (SAK) PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) (STUDI KASUS PADA TOKO AKBAR MARDIKA DI KOTA AMBON) - Suat, Siti Jumiati; Sososutiksno, Christina; Layn, Yuyun Yuniarti (Jurnal Akuntansi, 2023)
SAK EMKM is a financial statement that is regulated in accordance with the preparation standards and limitations in preparing financial statements for MSME actors. This is a responsibility that must be understood and implemented by MSME actors in order to provide convenience for MSMEs in supervising, evaluating and controlling financial conditions in their business. This study aims to find out (1) How the application of SAK EMKM in the preparation of financial statements for MSMEs Toko Akbar, (2) Whatare the problems faced by MSMEs in preparing financial statements in accordance with SAK EMKM. The type of research used in this study is a qualitative descriptive approach. The data collection techniques used are observation, interviews, and documentation. Where the object of research is MSMEs Toko Akbar which was established in 2019. Toko Akbar is located in Mardika market in Ambon City and sells glassware. The results showed: (1) Toko Akbar MSMEs already know accounting even though the application of accounting and financial statements that have been presented manually and simply, Toko Akbar MSMEs have implemented EMKM SAK in the preparation of their financial statements, (2) The obstacles faced by Toko Akbar MSMEs in preparing their financial statements are not having human resources who have the ability to compile financial statements and Toko Akbar MSMEs do not have computers, This is what becomes an obstacle because the application or software cannot be used.